Prognostic Value of the Systemic Immune-Inflammation Index and Prognostic Nutritional Index in Patients With Medulloblastoma Undergoing Surgical Resection - Zhu, Sihan; Cheng, Zhuqing; Hu, Yuanjun; Chen, Zhenghe; Zhang, Ji; Ke, Chao; Yang, Qunying; Lin, Fuhua; Chen, Yinsheng; Wang, Jian (Frontiers in Nutrition, 2021)
Background: The progression and metastasis of cancers are associated with systematic immune inflammation and nutritional dysfunction. Therefore, our study aimed to evaluate immune inflammation and nutritional index prognostic significance in medulloblastoma (MB) patients. Methods: We retrospectively analyzed 111 MB patients between 2001 and 2021 at our institution. The optimal cut‐off values for systemic immune inflammation index (SII), neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte counts ration (MLR), and prognostic nutritional index (PNI) were evaluated with receiver operating characteristic (ROC) curve analysis. Clinical characteristics and SII, NLR, MLR, and PNI were tested with the Pearson’s χ2 test. Kaplan-Meier survival curves and Cox Proportional Hazards model were used to evaluate the effects of immune inflammation and nutritional index on overall survival (OS). Result: ROC curve analysis determined the optimal SII, NLR, MLR, and PNI cutoff values of 2278, 14.83, 0.219, and 56.5 which significantly interacts with OS, and divided the patients into two groups. Comparative survival analysis exhibited that the high-SII cohort had significantly shorter OS (P=0.0048) than the low-SII cohort. For univariate analysis, the results revealed that preoperative hydrocephalus, SII, Albumin-Bilirubin score (ALBI), and coSII-PNI were predictors of OS (P<0.05). In multivariate analysis, preoperative hydrocephalus (P<0.001), ALBI (P=0.010), SII (P<0.001), and coSII-PNI (P<0.050) as independent prognostic factors were significantly correlated with OS. Conclusion: The preoperative SII, ALBI, and coSII-PNI serve as robust prognostic biomarkers for MB patients undergoing surgical resection.